“Estudio para mejorar los índices de calidad y confiabilidad del sistema eléctrico de la cooperativa de ahorro y crédito 9 de Octubre Ltda. Agencia Mulalillo” - Grefa, Anthony Leandro (2022)
The present technological proposal deals with the study to propose a solution to then quality and reliability indexes of the electrical system in the “9 de Octubre Ltda. Agencia Mulalillo” Credit Union, which aims to present a proposal to improve the electrical system. The study began with the collection of data detailing the number of transformers with their main parameters and users, using the web gateway Geo portal, through a network analyzer data on electricity consumption was obtained, with it was carried out the survey of information from the connection, with this data was obtained the current rates of energy demand. In order to improve the efficiency of the electric system service, the best alternative was the implementation of a transformer designated only for the entity, which allows mitigating the interruptions and disturbances of the service connection. The simulation of results continued, showing the new indicators with excellent results of the electric supply. After entering the demand data into the ETAP simulation software, the appropriate transformer was determined, for which the technical and economic proposals were presented, which improves the electrical parameters in the Credit Union, demonstrating that the project is viable and by improving the efficiency of the electrical service, the objectives are sustainable both technically and economically